In Vitro Antioxidant And Alpha-Glucosidase Inhibitory Activities Of Fruit Extracts From Seven Species Of Citrus - Henrietta, Ikwunne Helen (2018)
The in vitro α-glucosidase inhibitory and antioxidant activities, total phenolic and vitamin C contents of the pure juices (squeezed from the pulps), peel and pulp extracts from siix Citrus fruits that are grown in Malaysia, which are Citrus aurantifolia, Citrus grandis var. Tambun (PO52) and var. Penang Merah (PO5), Citrus hystrix, Citrus latifolia, and Citrus madurensis together with Citrus limon from Spain were determined in this comparative study. This is owing to the fact that these Citrus species that can be found in Malaysia has never been comparatively studied. The peels are mostly studied while the pulps and the juices are given less attention. The fresh and dried peel and pulp samples were extracted using methanol, ethanol and distilled water while 80% methanol was used for the extraction of crude extracts from dried peels and pulps. The result obtained from 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay revealed the highest free radical scavenging activity (96.14 ± 0.30%) of the methanol extract of dried peel of C. limon (at 100 mg/mL). The methanol extract of dried peel (at 100 mg/mL) and the juice of C. grandis var. Tambun (PO52) shared the highest ferric-reducing antioxidant power (FRAP) at 85.03 ± 6.32% and 84.29 ± 0.40%, respectively. The ethanol extract of fresh peel of C. grandis var. Penang Merah (PO5) exhibited the highest metal chelating activity at 98.85 ± 0.82%. Among the juices, the juice of C. grandis var. Tambun (PO52) gave the highest total phenolic content (TPC) of 14956.34± 152.65 μg gallic acid equivalent (GAE)/g juice. The distilled water extract of dried peel of C. limon gave the highest TPC at 33148.87 ± 124.46 μg GAE/g fresh weight of sample.